MENENTUKAN QUALITAS LULUSAN DENGAN PROBABILITAS QUOTA KELAS DAN LULUSAN PROGRAM STUDI MENGGUNAKAN PENDEKATAN MODEL LOGISTIC REGRESSION - Maxsi Ary (Paradigma, 2012)
Human resources (HR) is one of thesuccess factorsin the economy, how to createquality human resources andskillsas well ashighly competitivein theglobalcompetition. The education levelof the workforceis stillrelativelylow. Educational structureof Indonesia's workforceis stilldominated byprimary educationis about63.2%. The issueraisedisto determinethe probabilityofagoodcourse/ notwith alook at someratio ofgraduatesby the number ofstudentsperclass, the size of thequota-class (largeor small) usinglogistic regressionmodels. Dataobtained from thedata retrievalprogram of studybased on the numberof students andgraduatesin 2010. Processingdata usingSPSS.The results ofthe analysisby assessingmodel fitandwill be giventhe  resultsforeachmodel fit. Starting with thehypothesisforassessingmodel fit, statistical-2LogL, CoxandSnell's RSquare, Hosmer andLemeshow's Goodness ofFitTest,and theclassification table.The results ofthe analysisusingSPSSwas intended as a means of measuring quality of graduate course ata university, college,oracademy, whether or notbased onthe ratio ofthe number of graduatesandthe classquota.Keywords: The class quota, probability, logistic regression